Improve Students' Assertive Behavior using Assertive Training Techniques in Tenth Grade Students of Adhyaksa Jambi - Joni Afri; Freddi Sarman; Rully Andiyaksa (Pedagogy Review, 2023)
Abstract: The hypothesis proposed in this study is that there is a change or increase in students' assertive behavior after being given the treatment of group counseling services using assertive training techniques. This study uses quantitative methods. This type of research is pre-experiment, using the one group pretest posttest design. Selection of subjects using purposive sampling method. The number of research subjects was eight people with the category of assertive (moderate) and low behavior. This research was conducted in Adhiyaksa High School, the instrument used was the scale of assertive behavior with a Likert scale model. Data were analyzed using nonparametric statistical techniques that used the Wilcoxon Signed Ranks Test. The results showed that the pretest score was 99.125 and posttest 134.625. Then to test the hypothesis obtained Asymp results. Sig. (2-tailed) 0,005 which means under alpha 0,05 (0,005 less than 0,012) thus Ho can be interpreted rejected and Ha accepted. Based on the results of this study, it was concluded that there was a change or an increase in the assertive behavior of students after being given the treatment of group counseling services through Assertive Training techniques. Keywords: group counseling, assertive training, assertive behavior